A Design to Improve the Quality of OVO Electronic Money Payment Services in Tokopedia using IPA and PGCV - Eki Septiani; Eko Pujiyanto; Muhammad Hisjam (Jurnal Teknik Industri, 2020)
Currently, many online payment applications have sprung up in the community. This requires online payment application providers to compete in providing the best service for the community. This study aims to design an increase in the service quality of the OVO online payment application in Indonesia. This research applied Importance Performance Analysis (IPA) and Potential Gain in Customer Value (PGCV) methods to map the performance of service attributes and determine the priority service attributes for improvement. Based on the research conducted, the use of IPA and PGCV methods has been successfully utilized to map the performance of service attributes and determine priority attributes that should be improved.